Anticancer Activity Of Guava Leaf Extract (Psidium Guajava) - Tarizza Puspa Anggrelia, Tarizza Puspa Anggrelia; Icasia Carolina Dewi, Icasia Carolina Dewi; Ria Lestari Herawati, Ria Lestari Herawati; Sovia Maulina Azkiyah, Sovia Maulina Azkiyah; Ana Fatmah Az Zahro, Ana Fatmah Az Zahro; Ramadhan Putra Maulana, Ramadhan Putra Maulana; Agustinus Alfred Seran, Agustinus Alfred Seran; Ivan Charles S.Klau, Ivan Charles S.Klau; Arista Wahyu Ningsih, Arista Wahyu Ningsih (Al Makki Publisher, 2024)
Free radicals are chemical compounds that are highly reactive and have the possibility of being detrimental to the body's cells. At high levels, free radicals can pose a serious risk to health, inflicting damage to major components of cells. Cell damage caused by free radicals, especially to Deoxyribonucleic Acid (DNA), can result in the development of cancer and other health problems. Guava seed leaves (Psidium guajava) are the focus of research because of their potential in reducing the growth of breast cancer cells. The study details the results of two literature review studies that support this claim. The bioactive compounds such as polyphenols, flavonoids, phenolic acids, and ascorbic acid found in guava seeds have been linked to antioxidant and anti-inflammatory properties. The first study by showed that guava leaf extract has anti-proliferative activity against breast cancer cells (MDA-MB-231 and MG-63). The second study highlighted the cytotoxic activity of 70% ethanol extract from guava leaves against T47D breast cancer cells. The results of both studies showed that guava seeds have the potential to inhibit the growth of breast cancer cells, indicating a possible role for guava seeds in breast cancer prevention strategies.